2011
DOI: 10.1177/147323001103900616
|View full text |Cite
|
Sign up to set email alerts
|

Imbalance of Interleukin-18 and Interleukin-18 Binding Protein in Children with Henoch-Schönlein Purpura

Abstract: The balance between interleukin-18 (IL-18) and its endogenous antagonist, IL-18 binding protein (IL-18BP), was evaluated in children with Henoch-Schönlein purpura (HSP). Plasma IL-18 and IL-18BP levels and peripheral blood mononuclear cell IL-18 mRNA expression were significantly higher in patients with active HSP ( n = 30) than in healthy controls ( n = 20); IL-18BP mRNA expression was similar in active HSP and controls. Plasma levels and mRNA expression of IL-18 and IL-18BP in patients in remission ( n = 19)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…Our results demonstrate the absence of a significant difference in circulating levels of IL‐18 between subjects with HSP and healthy controls. Wang et al reported higher IL‐18 and IL‐18 binding protein (IL‐18BP) levels in subjects with HSP than in controls and did not observe any significant difference in IL‐18 levels between patients with active disease and those in remission. In our study we observed a significant decline in IL‐18 levels with remission.…”
Section: Discussionmentioning
confidence: 99%
“…Our results demonstrate the absence of a significant difference in circulating levels of IL‐18 between subjects with HSP and healthy controls. Wang et al reported higher IL‐18 and IL‐18 binding protein (IL‐18BP) levels in subjects with HSP than in controls and did not observe any significant difference in IL‐18 levels between patients with active disease and those in remission. In our study we observed a significant decline in IL‐18 levels with remission.…”
Section: Discussionmentioning
confidence: 99%
“…Wang et al showed a significantly higher level of IL-18 and IL-18 binding protein (IL-18BP) in active IgAV. They also showed a higher level of IL-18 in the acute phase compared with remission [39]. The elevated concentration of IL-18, which affects Th17 maturation and Th2 differentiation, may cause the above-mentioned increased proportions of the Th17 and Th2 in IgAV patients.…”
Section: Discussionmentioning
confidence: 91%
“…Furthermore, serum or plasma levels of IL-18 were significantly higher in patients with IgA vasculitis than in controls and the activity of IgA vasculitis is associated with the titer of IL-18 (Wang et al 2011;Mahajan et al 2013). The imbalance of IL-18 and IL-18 binding protein, which is endogenous antagonist of IL-18, may promote inflammation in IgA vasculitis (Wang et al 2011). The susceptibility to IgA vasculitis by specific IL-18 gene promoter polymorphisms was previously suggested (Torres et al 2010).…”
Section: Discussionmentioning
confidence: 92%
“…The skin biopsy finding of IgA vasculitis in the acute phase revealed the positivity of IL-1 immunohistochemical staining in the nucleated epidermal layer (Besbas et al 1997), and rs16944 genetic variant of IL-1β may be a genetic marker of severe renal manifestation of IgA vasculitis (Lopez-Mejias et al 2016). Furthermore, serum or plasma levels of IL-18 were significantly higher in patients with IgA vasculitis than in controls and the activity of IgA vasculitis is associated with the titer of IL-18 (Wang et al 2011;Mahajan et al 2013). The imbalance of IL-18 and IL-18 binding protein, which is endogenous antagonist of IL-18, may promote inflammation in IgA vasculitis (Wang et al 2011).…”
Section: Discussionmentioning
confidence: 96%